2015
DOI: 10.1111/hsc.12308
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring parental perspectives and involvement in health visiting services during the Health Visitor Implementation Plan in the South West of England

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
9
0
2
Order By: Relevance
“…Parents respond favourably to well-informed, encouraging, resourceful providers who respect their clients' knowledge and beliefs (Corr et al, 2015;Fenwick et al, 2013;Sheehan et al, 2009). These findings also correspond with international research which emphasises the value of timely responsive support, especially for parents experiencing psychosocial stresses or problems (Brook & Salmon, 2017;Cowley et al, 2015). Respondents often cited examples related to support with breastfeeding and with personal health issues particularly mental health.…”
Section: Discussionsupporting
confidence: 72%
“…Parents respond favourably to well-informed, encouraging, resourceful providers who respect their clients' knowledge and beliefs (Corr et al, 2015;Fenwick et al, 2013;Sheehan et al, 2009). These findings also correspond with international research which emphasises the value of timely responsive support, especially for parents experiencing psychosocial stresses or problems (Brook & Salmon, 2017;Cowley et al, 2015). Respondents often cited examples related to support with breastfeeding and with personal health issues particularly mental health.…”
Section: Discussionsupporting
confidence: 72%
“…Increasing caseloads of greater complexity result in a lack of time spent with families which has been shown to be a significant barrier to effective FFP [ 43 ]. Personal experiences of the home visitor can also shape their identity as a professional [ 61 ]. Some studies within mental health nursing have shown that personal experience of mental illness can have a positive influence on their understanding and relationship with service users [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA revealed that personal experience of mental illness had a signi cant effect on FFMHPQ scores, however variables such as, age, parental status, time since registration, and being in a specialist position had no effect on FFMHPQ scores. Health visitors' personal experiences can in uence their identity as a professional (24). In addition, there is some evidence to suggest that personal traits such as empathy (34) sense of coherence (35), conscientiousness, and emotional stability (36) are factors which in uence practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, new roles within specialist perinatal and infant mental health visiting are on the increase, and have received substantial funding (15,23). With many believing that these specialist roles will play a valuable part in reducing the incidence and impact of maternal mental illness in the perinatal period (23,24). Furthermore, it has been shown that health visitors' personal experiences can also shape their identity as a professional (25), with studies within mental health demonstrating that personal experience of mental illness can have a positive in uence on understanding and establishing positive relationships with service users (25, 26).…”
mentioning
confidence: 99%